Injuries in martial arts and combat sports - preliminary results of research - Kudlacz, M.; Cynarski, W. (Archives of Budo, 2007)
Study aim: At present there are sports with so-called high degree of risk connected with practicing them. This group includes, among others, combat sports. Probably the main argument supporting this approach to them was the essence of rivalry - direct combat of two competing sports persons. Almost all injuries connected with sport are caused by mechanical energy. Damages being a consequence of an impact are called injuries. The main aim of the study was estimating and evaluating the level of injuries in different martial arts and combat sports. Material/methods: The research has been conducted on a target group of 282 practitioners of various martial arts and combat sports. As it happens in the environment of people doing sports, the majority of respondents were males 257 compared to 25 women. (However, in statements by only two women there is information about injuries.) Those are contestants being at the top in the world, very successful in their sports. Among them there are Olympic, world and European champions. Among the practitioners of far eastern martial arts there are many holders of high and the highest master`s degrees of `dan`. The survey has been conducted with contestants at various ages among whom some fi nished their professional careers. There are also data concerning deceased people which had been collected earlier. The tool used here has been the `budo questionnaire` consisting of fi ve open questions. It is very important to note that some practitioners have done more than one martial art or combat sport. Results: Only 11.1% have not sustained any injury. Among all combat sports and martial arts the most frequent injuries have been broken bones (21%) and damages of knee ligaments (16%). The most frequent reason for injuries has been sporting fi ght 68%. However, most often (43%) training fi ght contributed to injuries than competition fi ght (25%). During training 21% of injuries occurred. In 3 cases (5.5%) injuries resulted in the end of sporting career. Usually this was caused by knee injuries. Conclusions: Injury sustainability in martial arts and combat sports at the stage of professional training is relatively high. The most frequent injuries in martial arts and combat sports are broken bones (usually limbs). The most frequent place of injuries is the head.